Patrimoine/cultural heritage in France and Ireland - Maher, Eamon; O'Brien, Eugene 1958- (Peter Lang, 2019)
This collection of essays explores the concept of patrimoine, a French word used to denote cultural heritage, traditional customs and practices ? the Gaelic equivalent is dúchas ? and the extent to which it impacts on France and Ireland. Borrowing from disciplines as varied as sociology, cultural theory, literature, marketing, theology, history, musicology and business, the contributors to the volume unearth interesting manifestations of how patrimoine resonates across cultural divides and bestows uniqueness and specificity on countries and societies, sometimes in a subliminal manner.00Issues covered include debt as heritage, Guinness as a cultural icon of ±Irishness?, faith-based tourism, the Huguenot heritage in Ireland, Irish musical inheritances since Independence, Skellig Michael and the commodification of Irish culture.
Keywords: Tradition; Tourismus; Werbung; Kulturerbe; Irland; Frankreich; Aufsatzsammlung